2010
DOI: 10.21608/eajbsz.2010.15890
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Atrazine on Levels of Pituitary–testis Hormones in Adult Male Rat

Abstract: Objective(s): Atrazine is a widely used herbicide in agriculture. In the present study, the effects of this herbicide on the levels of pituitary-testis hormones in adult male rats were investigated. Materials and Methods: In total, 40 male Wister rats were used. These animals were randomly divided into five groups of eight: the control group which was left untreated, the sham group receiving solvent, and three experimental groups receiving (100mg/kg), (200mg/kg) and (400mg/kg) dosages of Atropine, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Animal studies have indicated that ATR exposure reduces pituitary-testis hormone (luteotropic hormone, testosterone and follicle-stimulating hormone) levels, increases free triiodothyronine [ 17 , 18 , 19 ], and affects nervous system function. In addition, ATR induces ovarian functional changes via the regulation of hypothalamic catecholamines, especially norepinephrine (NE) and dopamine (DA) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have indicated that ATR exposure reduces pituitary-testis hormone (luteotropic hormone, testosterone and follicle-stimulating hormone) levels, increases free triiodothyronine [ 17 , 18 , 19 ], and affects nervous system function. In addition, ATR induces ovarian functional changes via the regulation of hypothalamic catecholamines, especially norepinephrine (NE) and dopamine (DA) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have also shown decreases in FSH in male rats and female rats exposed to 100, 200, or 400 mg/kg atrazine. This finding is expected based on the relationship of FSH to GnRH with studies in zebrafish confirming a decrease in GnRH after an embryonic exposure to 0.3, 3, or 30 ppb (µg/L) atrazine via immersion [ 26 , 48 ]. Overall, the cumulative body of research in this area confirms a wide range of atrazine exposure doses over short and longer term durations attenuates LH surge and disrupts estrous cyclicity.…”
Section: Effects Of Atrazine On Major Neuroendocrine Hormonesmentioning
confidence: 73%
“…The results showed that after treatment with both low and high doses of atrazine during 15 & 30 days periods, there is a significant decrease in FSH level in male rates, Similar to (Mokhtari, 2010) and inconsistent with (Yang, 2014), also showed a significant decrease in FSH level in female rates similar to (Bohn T., 2011) but our results are inconsistent with (Bohn T., 2011) in results of LH level where he found a decrease in LH level and our results didn't show any difference in the hormone level with a control group.…”
Section: Discussionmentioning
confidence: 84%